Selection of a structural strength criterion for inhomogeneous silica rod on the basis of full-scale and computational experiments - Trufanov, Aleksandr Nikolaevich; Lesnikova, Yulia Igorevna; Trufanov, Nikolay Aleksandrovich; Smetannikov, Oleg Yurievich (Computational Continuum Mechanics, 2016)
We consider the problem of estimating the strength properties of heterogeneously doped silica glass structures by the example of a stress applying rod for preform of the Panda-type polarization-maintaining optical fiber. The methodology of structural strength criteria selection is based on a combination of computational and full-scale experiments. In this case, the criteria characteristics indirectly take into account many difficult-to-measure factors that affect the strength of structures: scale factor, doping inhomogeneity, dispersion of strength, influence of technological operations on the quality of surface treatment and formation of surface and internal defects, technological residual stresses, etc. To analyze the strength of the article consistently, we have solved the following problems. Residual stresses in the rods were determined numerically taking into account the heterogeneity of thermo-mechanical characteristics. Full-scale three-point bending experiments on loading rods to fracture were performed. The stress-strain state of rods (including residual stress) was predicted during the fracture experiment. The calculated stress and strain fields corresponding to the action of the fracture load measured in the experiment were analyzed. It has been found that, as a criterion of the structural strength of inhomogeneously doped silica rod, a criterion of maximum principal strains can be used which gives a fairly good agreement with experimental data. For preform of the stress applying rod for the Panda-type polarization-maintaining optical fiber, a specific value for ultimate tensile strain was determined, and the area of maximum deformation at the interface between doped area and pure silica, which is the source of initiation and formation of cracks, was identified.